(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the importance of intercultural communication in the context of globalization and the need to foster it within the education system. It describes modern pedagogical technologies aimed at developing intercultural dialogue, including interactive methods, project-based learning, case studies, and virtual communication. The article emphasizes the role of these technologies in cultivating tolerance, respect, empathy, and global thinking among students. Practical recommendations for applying these approaches in educational practice are also provided.